Pharmacokinetics and Pharmacodynamics Estimation of Eculizumab in a 2-Year-Old Girl With Atypical Hemolytic Uremic Syndrome: A Case Report With 4-Year Follow-Up - Saida, Ken; Fukuda, Tsuyoshi; Mizuno, Kana; Ogura, Masao; Kamei, Koichi; Ito, Shuichi (Frontiers in Pediatrics, 2019)
Background: Eculizumab has dramatically changed poor outcomes of complement-mediated atypical hemolytic uremic syndrome as first-line treatment. Discontinuation of eculizumab remains challenging, and doctor’s visits every 2 weeks for intravenous injection because of standard dosing protocols is a huge burden. The Ultra-high cost of eculizumab is also an issue. We attempted to establish a personalized dosing regimen of eculizumab based on pharmacokinetics and pharmacodynamics in a 2-year-old girl with atypical hemolytic uremic syndrome with a C3 mutation. Case presentation: She developed atypical hemolytic uremic syndrome at 5 months of age and was successfully treated with eculizumab. At 2 years of age, we measured eculizumab concentrations and performed pharmacokinetics and pharmacodynamics analysis to optimize her dosing protocol. Her blood concentrations at every 2-, 3-, and 4-week intervals were simulated. Pharmacokinetics analysis showed that her eculizumab clearance was 40% lower than the population mean reported for atypical hemolytic uremic syndrome. Pharmacokinetic simulation suggested that the 2- and 3-week interval regimen could be sufficient to achieve an efficient trough concentration (>100 µg/mL). We simulated her individual pharmacokinetics profile at 4 years of age with consideration of her growth, which still showed complete inhibition of the alternative complement pathway with the 3-week interval regimen. We continued the 300-mg eculizumab infusion every 3 weeks while CH50 levels were constantly maintained at undetectably low concentrations with no recurrence until 6 years of age. Conclusions: Pharmacokinetics and pharmacodynamics estimation was useful for establishing a personalized dosing regimen for eculizumab and reducing the patient’s burden and high medical costs.